In situ wet pharmaceutical granulation captured using synchrotron radiation based dynamic micro-CT - Xiao Fan Ding; Sima Zeinali Danalou; Lifeng Zhang; Ning Zhu (Journal of Synchrotron Radiation, 2023)
Synchrotron radiation based dynamic micro-computed tomography (micro-CT) is a powerful technique available at synchrotron light sources for investigating evolving microstructures. Wet granulation is the most widely used method of producing pharmaceutical granules, precursors to products like capsules and tablets. Granule microstructures are known to influence product performance, so this is an area for potential application of dynamic CT. Here, lactose monohydrate (LMH) was used as a representative powder to demonstrate dynamic CT capabilities. Wet granulation of LMH has been observed to occur on the order of several seconds, which is too fast for lab-based CT scanners to capture the changing internal structures. The superior X-ray photon flux from synchrotron light sources makes sub-second data acquisition possible and well suited for analysis of the wet-granulation process. Moreover, synchrotron radiation based imaging is non-destructive, does not require altering the sample in any way, and can enhance image contrast with phase-retrieval algorithms. Dynamic CT can bring insights to wet granulation, an area of research previously only studied via 2D and/or ex situ techniques. Through efficient data-processing strategies, dynamic CT can provide quantitative analysis of how the internal microstructure of an LMH granule evolves during the earliest moments of wet granulation. Here, the results revealed granule consolidation, the evolving porosity, and the influence of aggregates on granule porosity.